Records Committee review for rare bird sighting of Lesser Black-backed Gull near Jester Park at Saylorville Reservoir, 1988 - Dinsmore, Stephen J.et al (1988)
Records Committee review for a Lesser Black-backed Gull near Jester Park at Saylorville Reservoir in Polk County, IA on November 15, 1988. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed